Kasus Pernikahan Sejenis dalam Perspektif Hukum Moral John Calvin - Imelda Ginting (Reformed Center for Religion and Society, 2016)
ABSTRACT: This article will firstly discuss in brief about the fact of the LGBT (Lesbian, Gay, Bisexual, and Transgender), situational ethics as its foundation for justification, and the community which fights for the legalization of the same-sex marriage. In this section, I will explain on the foundation which is used for justification of same-sex marriages legalization. After that, I will give a review on John Calvins moral law to assess whether the foundation which is used for that justification is appropriate. The finding of this article is that same-sex marriages legalization does not have an appropriate foundation according to Calvins moral law. Therefore, this cannot be accepted by the church.Â KEYWORDS: same-sex marriage, moral law, John Calvin.